Antitumor activities of PSMA×CD3 diabodies by redirected T-cell lysis of prostate cancer cells. (January 2013) - Baum, Volker; Bühler, Patrick; Gierschner, Dorothee; Herchenbach, Dieter; Fiala, Gina J; Schamel, Wolfgang WA; Wolf, Philipp; Elsässer-Beile, Ursula
Aim: Although prostate cancer is one of the most commonly diagnosed malignancies in men, there is no effective curative therapy for the advanced disease. Therefore, the aim of the present study was to generate prostate-specific membrane antigen (PSMA)×CD3 diabodies as a novel treatment option for this tumor.Methods: A PSMA×CD3 diabody and a covalently linked single-chain diabody were constructed from the anti-PSMA single-chain Fv fragment D7 and an anti-CD3 single-chain Fv fragment. The fusion proteins were periplasmatically expressed in Escherichia coli . The binding properties were tested on PSMA-expressing C4-2 prostate cancer cells and CD3 + Jurkat cells by flow cytometry. For in vitro functional analysis, a cell viability assay was used. T-cell activation was determined by flow cytometry. In vivo activity of the diabody was tested in SCID mice reconstituted with human peripheral blood lymphocytes bearing C4-2 tumor xenografts.Results: Bacterial expression levels were significantly higher for the diabody (1–1.5 mg/l culture) compared with the single-chain diabody (0.2–0.4 mg/l culture). Specific binding on CD3-expressing Jurkat cells and PSMA-expressing C4-2 cells was shown with both diabody formats. In vitro, both diabodies proved to be potent agents for retargeting human CD4 + and CD8 + lymphocytes to lyse C4-2 prostate cancer cells. The formation of conjugates between T cells and target cells with clustering of the diabody at sites of interaction could be shown. SCID mice reconstituted with human peripheral blood lymphocytes bearing C4-2 tumor xenografts with the diabody showed an efficient inhibition of tumor growth.Conclusion: Both diabody formats showed a highly efficient and specific T cell-mediated killing of prostate cancer cells and are encouraging for further development in preclinical and clinical studies.